Sustainable transport: challenges and opportunities - Banister, D (Taylor and Francis, 2009)
This paper explores sustainable transport within the European Union (EU), arguing that a strong sustainable transport definition needs to be used if targets set at Kyoto are to be achieved. The EU strategy is now (2006) based on modal shift, decoupling and technological innovation, weakening the more radical strategy set up in 2001. It seems that expansion of the EU, lower levels of growth, and the possibilities of continuing high costs of oil have resulted in changing priorities, but above all travel demand has continued to grow. The Kyoto targets are becoming much harder to reach. The paper then outlines the three groups of measures that have been promoted, looking at (1) technology and pricing, (2) regulation, taxation and congestion charging, and (3) land use, development and planning, arguing that strong action is required on all three sets of options. Even then, there is an additional requirement, namely the need to gain public acceptability through information, marketing and engagement so that positive outcomes can be matched up with policy intentions. Real progress towards reducing carbon emissions is possible provided that mutually supporting measures are taken, with political commitment to real change and public support for that change.